The Effect of Time Budget Pressure, Integrity, and Motivation on Auditor Performance: A Case Study on the Development Supervisory Board Special Region of Yogyakarta Representative - Nadhira Elmaghani Marits; Indra Kusumawardhani (Journal of International Conference Proceedings, 2024)
This study aims to examine and provide empirical evidence on the effects of time budget pressure, integrity, and motivation on auditor performance. The research was conducted at the Representative Office of the Development and Financial Supervisory Board located in the Special Region of Yogyakarta, Indonesia. A quantitative research method was employed to systematically analyze the relationships between the variables. Primary data was collected through online questionnaires administered to respondents via Google Forms, ensuring convenience and accessibility. The study utilized a purposive sampling technique, selecting respondents based on specific criteria. The criteria included auditors who had successfully completed auditor training and education programs and possessed a minimum of one year of work experience in the field. A total of 61 respondents participated and completed the questionnaire, providing a robust dataset for analysis. The findings of the study revealed that time budget pressure, integrity, and motivation each have a significant and measurable impact on auditor performance, highlighting their importance in the auditing profession